Different complexes are formed on the 3' end of histone mRNA with nuclear and polyribosomal proteins. - Pandey, N B (1991)
Specific protein-RNA complexes are formed by incubating a synthetic histone mRNA 3' end (a 30 nucleotide stem-loop structure) RNA with extracts of either nuclei or polyribosomes. The complex formed between the stem-loop and nuclear proteins has a lower electrophoretic mobility than the complex formed between the stem-loop and polyribosomal proteins. Binding of the synthetic 3' end by both polyribosomal and nuclear proteins is abolished when two of the conserved uridine residues in the loop are replaced with adenosines. UV crosslinking of the protein complexes to the synthetic RNA resulted in transferring radiolabel to similar sized proteins, 50 kD, in both the nuclear and polyribosomal extracts.